Calmodulin-Mediated Cell Cycle Regulation: New Mechanisms for Old Observations - Choi, Jaehyun; Husain, Mansoor (Cell cycle (Georgetown, Tex.), 2006)
The significance of divalent calcium ions (Ca2+) to cell cycle progression has been a subject of study for several decades, with a regulatory role for Ca2+ suggested in distinct cell types and multiple organisms. Our interest in proliferative vascular diseases led us to focus on mammalian vascular smooth muscle cells (VSMC) in particular, in which we and others had shown that a coordinate elevation in the intracellular free Ca2+ concentration is required for G1 to S phase cell cycle progression. However, the molecular basis for this Ca2+-sensitive cell cycle transition was not known.Our recent discovery of a functional protein-protein interaction between the late G1-active cyclin E1 and the major calcium signal-transducing factor Calmodulin (CaM) sheds new light on the mechanism(s) through which Ca2+ concentrations regulate cell cycle. Having identified a CaM-binding site on cyclin E1, our studies support a direct role for CaM in mediating Ca2+-sensitive cyclin E/cdk2 activity and G1 to S phase transitions in VSMC. The CaM binding site identified on cyclin E1 has a Kd for CaM consistent with that of known CaM-binding proteins, and is composed of a 22 amino acids N-terminal sequence that is highly conserved across several mammalian species. Deletion of this binding site abolished CaM binding and Ca2+-sensitive cyclin E/cdk2 activity.Here we provide our perspectives on the literature supporting a role for Ca2+ in cell cycle regulation, focusing on the evidence implicating CaM in this functionality, and discuss the potential for therapeutic modulation of CaM-dependent cell cycle machinery.